Profitabilitas, Leverage, Ukuran Perusahaan, Opini Audit dan Manajemen Laba - Chairunnisa, Adinda; Pahala, Indra; Nasution, Hafifah (E-Jurnal Akuntansi; Vol 32 No 11 (2022), 2022)
This study examines the influence of profitability, leverage, firm size, and audit opini on earnings management, in mining sector companies listed on the Indonesia Stock Exchange for the period of 2019-2021. The sampling technique that used in this research is purposive sampling method, and obtained 23 mining companies selected with a total 69 data.  Data analysis technique used multiple linear regression with SPSS version 25 program. The results show that profitability and firm size has a significant positive effect with earnings management, while leverage and audit opinion has an insignificant effect with earnings management. Further research can use other variables or by changing the proxies used in this study and by adding more sectors and years of research, so the scope of research data becomes wider. Keywords: Earnings Management; Profitability; Leverage; Firm Size; Audit Opinion